INVESTMENT INTEREST IN KENDARI COMMUNITY - Muhammad Afriansyah Hidayah; RR Tini Anggraeni (Journal of Islamic Economy and Business (JIsEB), 2023)
Investment is one of the development tools needed by a country to improve people's welfare. This study aims to determine the effect of financial literacy, accountability, religiosity, returns, and digital platforms on investment interest (an empirical study of the people of Kendari). The population in this study is the general public of Kendari City. The sampling technique used is random sampling technique, the selected sample is 156 respondents. Data was taken using the questionnaire method. The data analysis method used was multiple regression analysis with the help of SPSS version 25 software. The results showed that the coefficient of determination test obtained an adjusted R value of 59.2% while the remaining 40.8% was influenced by other variables not included in this study. Based on the results of multiple linear regression tests, the most dominant variable affecting investment interest is digital platforms.